Extreme Significant Wave Height Map of Indonesia Based on SEAFINE and ERA5 Database - Andojo Wurjanto; Julfikhsan Ahmad Mukhti; Hijir Della Wirasti (Journal of Engineering and Technological Sciences, 2021)
Significant wave height, , is one of the most utilized ocean parameters. Extreme  with 1-yearly and 100-yearly return periods are required for the design of most offshore structures. A previous study by Wurjanto, et al. (2020) attempted to utilize the SEAFINE database to develop extreme  maps of Indonesian seas. However, SEAFINE does not cover the eastern Indonesian seas. This study analyzed the extreme values from ERA5 data for Indonesian seas and utilized the data to complete the extreme  map previously developed by Wurjanto, et al. (2020). The ERA5  data on the eastern Indonesian seas as well as the central and western seas were extracted for validation purposes. The ERA5 extreme value was less than half the  value compared to the SEAFINE-based results in most intersecting areas. For the development of the map, we took the SEAFINE-based map from Wurjanto et al., which covers the western and middle Indonesian seas, and filled the eastern part with extreme ERA5  data. It was found that a wave height multiplying factor of 2.0 was the most suitable for ERA5 in the developed map to make a seamless wave height transition from SEAFINE to ERA5 data.